Potential toxicity of cashew nut shell liquid (CNSL) on adult Bactrocera dorsalis (Hendel) (Tephritidae) - Sainey Keita; Wan Fatma Zuharah (Journal of Taibah University for Science, 2023)
The oriental fruit fly, Bactrocera dorsalis (Hendel), is a serious pest of papaya in all the regions. Cashew nut shell liquid (CNSL) Anacardium occidentale L. is a by-product of the shell of the nut after the kernel has been extracted to utilize as an insecticide to control fruit flies. This study investigated the insecticidal activity of topically applied dichloromethane and hexane extracts of CNSL against B. dorsalis. The LC50 values for the dichloromethane extract represented a 2.54-fold increase in toxicity from 6 h to 24 h (2.18 × 104 ppm) versus a 2.38-fold increase for hexane extracts after 24 h (2.94 × 104 ppm), which mortality was significantly impacted by time and concentration (p < 0.01). A GC-MS analysis of the two extracts showed the presence of higher phenol and 3-pentadecyl-. The CNSL was found to possess insecticidal activity against B. dorsalis, hence could be evaluated in the field to further assess their potential for B. dorsalis control.